Enhancement for e-gallery system in National Art Gallery / Muhamad Nazri Mohd Yahya - Mohd Yahya, Muhamad Nazri (2007)
The research is to enhance the existing system in National Art Gallery. In order to enhance the existing system, the functionality of the existing must be captured. Software Requirement Specification (SRS) is used to capture the requirement to enhance the existing system. The interview session with Head Curator is to identify the problem with existing system. From the interviewing, the objective of research and solution of that problem is identified. In order to describe the artwork in more detail, the Categories for the Description of Work of Art (CDWA) are used. CDWA describes the content of art databases by articulating a conceptual framework for describing and accessing information about works of art, architecture, other material culture, groups and collections of works, and related images. The CDWA includes 512 categories and subcategories. The technique such direct manipulation also used in this research to enhance the system and make it more interactive for user to browse the E-Gallery. The technique is used to manipulate the artwork visual image display in artwork detail webpage. This technique can make the system more interactive than usual.